A ferric oxide / phosphomolybdic acid composite material and its preparation method and use

By using ferric trioxide/phosphomolybdate composite materials as catalysts, the problem of unsatisfactory photocatalytic degradation in the prior art and the difficulty in separation and reuse of catalysts is solved, and efficient degradation of methylene blue and potassium dichromate is achieved, and the catalyst is also able to achieve high-efficiency degradation of methylene blue and potassium dichromate. Stay stable during recycle use.

CN116273096BActive Publication Date: 2025-02-14JILIN INST OF CHEM TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211403437.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-10
Publication Date
2025-02-14
Estimated Expiration
2042-11-10

AI Technical Summary

Technical Problem

The prior art has problems in the photocatalytic degradation of methylene blue and potassium dichromate, and the catalyst is difficult to separate and reuse.

Method used

Using ferric oxide/phosphomolybdate composite material as catalyst, Fe2O3 nanoparticles and Dawson type phosphomolybdate P2Mo18 were prepared, and tetrabutyl ammonium bromide was combined as surfactant to form a simple preparation and high-efficiency photocatalysis. Composite material of performance.

Benefits of technology

The 99% degradation rate to methylene blue and 96% degradation rate to potassium dichromate solution was achieved, and the catalyst maintained stability during recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116273096B_ABST
    Figure CN116273096B_ABST
Patent Text Reader

Abstract

The invention discloses a ferric oxide / phosphomolybdic acid composite material and a preparation method and use thereof. Firstly, Fe2O3 nanoparticles and Dawson type phosphomolybdic acid P2Mo are prepared. 18 ; Tetrabutylammonium bromide was used as a surfactant to convert Dawson type P2Mo 18 The ferric oxide / phosphomolybdic acid composite material is prepared by compounding with Fe2O3 nanoparticles, and the preparation process is simple. The prepared ferric oxide / phosphomolybdic acid composite material can photocatalytically degrade methylene blue and potassium dichromate, and the degradation effect is good. The final degradation rate of methylene blue can reach 99%, and the degradation rate of potassium dichromate solution after adding methanol can reach 96%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts for photocatalytic degradation of methylene blue and potassium dichromate, in particular to a ferric oxide / phosphomolybdic acid composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of the global economy and human industrial civilization, energy crisis and environmental pollution have become serious problems faced by human survival. As a green and renewable energy, solar energy is inexhaustible. In particular, solar cells have become an important way to solve the energy crisis worldwide. Its development and use have attracted worldwide attention. Due to the urgent demand for low-cost and high-efficiency solar energy conversion products, the development of optoelectronic materials with application prospects is a current research hotspot. Organic dyes have good application potential in low-cost solar cells due to their structural diversity, high molar extinction coefficient, simple synthesis, and good broadband absorption in the solar spectrum. Methylene blue is a phenazine dye. Due to its highly delocalized π-π conjugated structure, it contains rich electrons and has good absorption in the UV-Vis region of the solar spectrum. It is widely used in hole transport materials and photosensitizers in solar energy conversion. The benzene ring in its structure is a difficult-to-degrade functional group. It is widely used in the dyeing of cotton and linen fabrics in the printing and dyeing industry and inorganic chemistry experiments in university laboratories. If it is directly discharged into the water without any treatment, dye wastewater and experimental sewage will cause serious water pollution, which will endanger human health.

[0003] In addition, the waste liquid produced by the industry is discharged into the environment, which has caused huge pollution, especially potassium dichromate, which is highly carcinogenic and difficult to remove (see Food Chem. Toxicol., 2007, 45, 2030-2039. Aquat. Toxicol., 2008, 87, 108-114.). The current method is generally to reduce it into non-toxic trivalent chromium ions. Adding a reducing agent may introduce new pollution sources and consume a lot of energy efficiency, so a photocatalytic method is generally used to reduce it, which can avoid introducing new pollution sources and save energy (see Appl. Catal. B: Environ., 2008, 84, 148-155. Appl. Catal. B: Environ., 2006, 62, 28-34.). At present, catalytic reactions are divided into homogeneous catalytic reactions and heterogeneous catalytic reactions. The advantages of homogeneous catalysis are high efficiency and low catalyst poisoning, but it is difficult to separate and reuse, which has become a huge problem it currently faces (see J.Am.Chem.Soc.2013,135,14500-14503). Heterogeneous catalysis is easy to separate, but it is prone to catalyst poisoning and has low catalytic efficiency.

[0004] The preparation and photocatalytic application of Keggin-type saturated phosphomolybdate and its coating materials disclosed in Chinese patent application No. 201710951848.6, and the synthesis of micro-nano polyacid PMo by hydrothermal synthesis 12 Then, the nano-precious metal silver particles were used as the matrix to synthesize the polyacid core-shell coating material Ag@PMo, which is rarely reported so far. 12 The methylene blue dye was degraded under simulated sunlight, and the effects of the initial concentration of the dye, the pH value of the solution and the added factor H2O2 on the decolorization and degradation effect were studied to determine the optimal treatment conditions, so as to fully utilize solar energy. However, the degradation effect was not ideal. Summary of the invention

[0005] The purpose of the present invention is to solve the deficiencies in the prior art and to provide a ferric oxide / phosphomolybdic acid composite material and a preparation method and use thereof.

[0006] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0007] The first object of the present invention is to provide a method for preparing a ferric oxide / phosphomolybdic acid composite material, comprising the following steps:

[0008] S1. Preparation of Fe2O3 nanoparticles and Dawson-type phosphomolybdic acid P2Mo 18 ;

[0009] S2, preparation of ferric oxide / phosphomolybdic acid composite material: take a Dawson type phosphomolybdic acid P2Mo with a weight ratio of 100: (1-10) 18 and Fe2O3 nanoparticles were dissolved in water, stirred and mixed thoroughly, and then 0.1 mol / L tetrabutylammonium bromide aqueous solution was added dropwise, the added volume of the tetrabutylammonium bromide aqueous solution was the same as the mentioned volume of the water, and the reaction was continued for 24 hours. After the reaction was completed, centrifugation was performed, and the mixture was washed with deionized water and ethanol and then dried in an oven at 40°C to obtain an iron trioxide / phosphomolybdic acid composite material.

[0010] Specifically, the specific steps of preparing Fe2O3 nanoparticles in step S1 are as follows:

[0011] 0.278 g of FeSO4·7H2O and 0.246 g of CH3COONa were dissolved in 40 mL of deionized water, and the mixture was stirred thoroughly to be uniform. The solution was transferred to a reactor and heated at 140°C for reaction for 2-24 h. After the reactor was cooled to room temperature, it was centrifuged, washed with deionized water and anhydrous ethanol, and then dried in an oven at 40°C. After drying, the mixture was transferred to a crucible, placed in a muffle furnace for calcination, and calcined at 500°C for 2 h to obtain Fe2O3 nanoparticles.

[0012] Specifically, in step S1, Dawson type phosphomolybdic acid P2Mo is prepared 18 The specific steps are as follows:

[0013] Dissolve 50g of Na2MoO4·2H2O in 225mL of deionized water, add 13-17ml of 85% H3PO4, and then add 3-6ml of concentrated hydrochloric acid to acidify, heat and reflux for 10h, cool the solution to room temperature, repeatedly add NH4Cl for recrystallization, and crystallize P2Mo 18 The ammonium salt was dried at 40 °C to obtain pure Dawson type phosphomolybdic acid P2Mo 18 .

[0014] Preferably, the heating reaction time for preparing the Fe2O3 nanoparticles is 12 hours.

[0015] Preferably, the Dawson type phosphomolybdic acid P2Mo 18 and Fe2O3 nanoparticles in a weight ratio of 100:5.

[0016] The second object of the present invention is to provide a ferric oxide / phosphomolybdic acid composite material prepared by the above method.

[0017] The third object of the present invention is to provide a use of an iron oxide / phosphomolybdic acid composite material, wherein the iron oxide / phosphomolybdic acid composite material is used as a catalyst for photocatalytic degradation of methylene blue and / or potassium dichromate.

[0018] Compared with the prior art, the present invention uses tetrabutylammonium bromide as a surfactant to convert Dawson type P2Mo 18 The ferric oxide / phosphomolybdic acid composite material is prepared by compounding with Fe2O3 nanoparticles, and the preparation process is simple. The prepared ferric oxide / phosphomolybdic acid composite material can photocatalytically degrade methylene blue and potassium dichromate, and the degradation effect is good. The final degradation rate of methylene blue can reach 99%, and the degradation rate of potassium dichromate solution after adding methanol can reach 96%. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a scanning electron microscope image of Fe2O3.

[0020] Figure 2 This is the X-ray powder diffraction pattern of Fe2O3.

[0021] Figure 3 This is the UV-visible spectrum of Fe2O3 and its band gap energy diagram.

[0022] Figure 4 This is the UV-visible spectrum of Fe2O3 and its band gap energy diagram.

[0023] Figure 5 It is Dawson type phosphomolybdic acid P2Mo 18 Infrared spectrum of .

[0024] Figure 6 It is Dawson type phosphomolybdic acid P2Mo 18 UV-visible spectrum of .

[0025] Figure 7 It is Dawson type phosphomolybdic acid P2Mo 18 Band gap energy diagram.

[0026] Figure 8 It is Dawson type phosphomolybdic acid P2Mo 18 Scanning electron microscope image of .

[0027] Fig. 9 It is Dawson type phosphomolybdic acid P2Mo 18 Cyclic voltammetry test diagram.

[0028] Fig.10 Infrared spectra of ferric oxide / phosphomolybdic acid composite materials with different proportions.

[0029] Fig.11 This is the UV-visible spectrum of the ferric oxide / phosphomolybdic acid composite material.

[0030] Fig.12This is the X-ray powder diffraction pattern of the iron oxide / phosphomolybdic acid composite material.

[0031] Fig.13 This is a scanning electron microscope image of the iron oxide / phosphomolybdic acid composite material.

[0032] Fig.14 This is the photoluminescence spectrum of the iron oxide / phosphomolybdic acid composite material.

[0033] Fig.15 Nyquist and Bode diagrams of different ratios of ferric oxide / phosphomolybdic acid: (a) Nyquist diagram; (b) Bode diagram.

[0034] Fig.16 Infrared spectra of the composite materials prepared by Fe2O3 with different reaction times.

[0035] Fig.17 UV-visible spectra of the composite materials prepared by Fe2O3 with different reaction times.

[0036] Fig.18 Photoluminescence spectra of the composite materials prepared by Fe2O3 with different reaction times.

[0037] Fig.19 Nyquist and Bode diagrams of the composite materials prepared with Fe2O3 at different reaction times: (a) Nyquist diagram; (b) Bode diagram.

[0038] Fig. 20 This is a data graph of the photocatalytic performance of ferric oxide / phosphomolybdic acid composite materials on different substrates.

[0039] Fig.21 The photocatalytic data of ferric oxide / phosphomolybdic acid composite material at different concentrations of methylene blue and its catalytic rate data: (a) photocatalytic performance diagram; (b) catalytic rate data diagram.

[0040] Fig. 22 The photocatalytic performance and catalytic rate data of ferric oxide / phosphomolybdic acid composite materials under different catalysts: (a) photocatalytic performance diagram; (b) catalytic rate data diagram.

[0041] Fig.23 The photocatalytic performance and catalytic rate data of ferric oxide / phosphomolybdic acid composite materials at different pH values ​​are shown in the figure: (a) photocatalytic performance graph; (b) catalytic rate data graph.

[0042] Fig.24 This is the degradation diagram of methylene blue of ferric oxide / phosphomolybdic acid composite material at pH 7.

[0043] Fig.25This is the experimental data of the photocatalytic degradation of methylene blue by ferric oxide / phosphomolybdic acid composite material.

[0044] Fig.26 This is the infrared comparison diagram of the cyclic experimental samples of photocatalytic degradation of methylene blue by ferric oxide / phosphomolybdic acid composite materials.

[0045] Fig. 27 This is the test data diagram of the photocatalytic degradation mechanism of methylene blue by ferric oxide / phosphomolybdic acid composite material.

[0046] Fig.28 Cyclic voltammetry test diagram and band gap energy diagram of Fe2O3: (a) cyclic voltammetry test diagram; (b) band gap energy diagram.

[0047] Fig.29 This is the mechanism diagram of photocatalytic degradation of methylene blue by ferric oxide / phosphomolybdic acid composite material.

[0048] Fig.30 This is the photocatalytic data of ferric oxide / phosphomolybdic acid composite material under different concentrations of potassium dichromate.

[0049] Fig.31 The photocatalytic data of potassium dichromate under different catalysts.

[0050] Fig.32 The photocatalytic data of potassium dichromate at different pH values.

[0051] Fig.33 This is the test data of the photocatalytic mechanism of photocatalytic degradation of potassium dichromate solution by ferric oxide / phosphomolybdic acid composite material.

[0052] Fig.34 The effect of different pH values ​​on the photocatalytic degradation of potassium dichromate solution by ferric oxide / phosphomolybdic acid composite material.

[0053] Fig.35 The effect of ferric oxide / phosphomolybdic acid composite materials with different Fe2O3 loading amounts on the photocatalytic degradation of potassium dichromate solution.

[0054] Fig.36 This is the experimental data of the photocatalytic cycle of the ferric oxide / phosphomolybdic acid composite material for photocatalytic degradation of potassium dichromate solution.

[0055] Fig.37 This is the cyclic infrared spectrum of the photocatalytic degradation of potassium dichromate solution by ferric oxide / phosphomolybdic acid composite material.

[0056] Fig.38 This is the mechanism diagram of photocatalytic degradation of potassium dichromate solution by ferric oxide / phosphomolybdic acid composite material. DETAILED DESCRIPTION

[0057] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.

[0058] Example 1

[0059] This embodiment specifically discloses a method for preparing a ferric oxide / phosphomolybdic acid composite material, comprising the following steps:

[0060] (1) Preparation of Fe2O3 nanoparticles:

[0061] Dissolve 0.278g FeSO4·7H2O and 0.246g CH3COONa in 40mL deionized water and stir for a while. Transfer the solution to a reactor and heat at 140℃. Adjust the reaction time, and the heating time is 2h, 6h, 12h, 18h, and 24h respectively. After cooling the reactor to room temperature, centrifuge, wash with deionized water and anhydrous ethanol, and dry in an oven at 40℃. Transfer the sample to a crucible, put it into a muffle furnace for calcination, and calcine at 500℃ for 2h to obtain Fe2O3 nanoparticles with different morphologies.

[0062] The Fe2O3 prepared in this example is characterized mainly by X-ray powder diffraction, UV-visible spectrometer, scanning electron microscopy and cyclic voltammetry. The scanning electron microscopy image of the Fe2O3 nanoparticles prepared in this example is as follows: Figure 1 As shown, the X-ray powder diffraction data of Fe2O3 nanoparticles is as follows Figure 2 As shown, the UV-visible spectrum of Fe2O3 nanoparticles and its band gap energy diagram are shown in Figure 3 , Figure 4 As shown. Figure 1 It can be seen that Figure 1 a, b, c, d, and e in the figure are scanning electron microscope images of Fe2O3 nanoparticles prepared under reaction times of 2h, 6h, 12h, 18h, and 24h, respectively. Under the condition of a reaction time of 2h, the prepared Fe2O3 is uniformly spherical with a diameter of about 50nm. When the reaction time reaches 6h, the Fe2O3 particles gradually become larger, forming spherical Fe2O3 with a diameter of 100nm. When the reaction time is extended to 12h, the spherical Fe2O3 particles gradually turn into hexagonal flake Fe2O3. The reaction time is further extended, and when the reaction time reaches 18h, a mixture of rod-shaped and block-shaped Fe2O3 is obtained. When the reaction time reaches 24h, block-shaped Fe2O3 nanoparticles with uniform morphology are obtained. By Figure 2It can be seen that the diffraction peak of the prepared Fe2O3 nanoparticles fully matches the peak position and peak intensity of the standard card PDF#99-0060, and the prepared Fe2O3 nanoparticles belong to the rhombohedral phase, wherein the intensity of (104) crystal plane, (110) crystal plane, and (116) crystal plane is the strongest. In the present embodiment, the effect of reaction time on the crystallinity of the prepared sample is discussed. It is found that although the positions of the diffraction peaks of different Fe2O3 prepared under the conditions of reaction time of 2h, 6h, 12h, 18h, and 24h do not change, the diffraction peak intensity is different. The peak intensity of the sample prepared under the reaction time of 2h, 6h, and 12h is stronger, the peak intensity of the sample prepared under the reaction time of 18h is relatively weak, and the peak intensity of the sample prepared under the reaction time of 24h is improved again compared with that of 18h, but the diffraction intensity of the sample prepared under the reaction time of 12h is still obviously weak. The XRD test results show that the sample prepared under the reaction time of 12h has a more ideal crystallinity. Depend on Figure 3 It can be seen from the UV-visible spectra of Fe2O3 with different reaction times that the UV absorption range of the five samples is 200-700nm. The Fe2O3 can successfully expand the light absorption range to the yellow-green light region and even the red light region, which can greatly improve the utilization rate of sunlight in the photocatalytic process. From the analysis of spectral intensity, it can be obtained that the peak intensity of the Fe2O3 sheet prepared with a reaction time of 12h is the highest, and the light absorption effect is better. The differences in the light absorption ranges of the five samples are relatively small. Using the Kubelka-Munk equation for conversion, further comparisons of the band gap widths of the five materials are made and it is found that Figure 4 It can be seen that the band gap widths of the five samples are between 1.95 and 2.02 eV. The band gap of the Fe2O3 nanomaterial prepared with a reaction time of 12 h is relatively wide, which can better inhibit the recombination of photogenerated electrons and photogenerated holes, improve the separation efficiency of photogenerated carriers, and thus promote the photocatalytic reaction.

[0063] (2) Preparation of Dawson-type phosphomolybdic acid P2Mo 18 :

[0064] Dissolve 50g Na2MoO4·2H2O in 225mL deionized water, add a certain amount of 85% H3PO4, and then add a certain amount of concentrated hydrochloric acid to acidify, and heat to reflux for 10h. After the solution is cooled to room temperature, add a certain amount of NH4Cl to crystallize P2Mo 18 The ammonium salt of Dawson type phosphomolybdic acid P2Mo was obtained by repeatedly adding NH4Cl for recrystallization and drying the sample at 40°C. 18 .

[0065] The Dawson type phosphomolybdic acid P2Mo prepared in this example 18The characterization was mainly carried out by infrared spectroscopy, UV-visible spectrometer, scanning electron microscope and cyclic voltammetry test. The Dawson type phosphomolybdic acid P2Mo prepared in this example 18 The infrared spectrum of Figure 5 As shown, Dawson type phosphomolybdic acid P2Mo 18 The UV-visible spectrum and band gap energy diagram of Figure 6 , Figure 7 As shown, Dawson type phosphomolybdic acid P2Mo 18 Scanning electron microscopy images of Figure 8 As shown, Dawson type phosphomolybdic acid P2Mo 18 The cyclic voltammetry test diagram is as follows Fig. 9 shown.

[0066] from Figure 5 It can be seen that polyoxometalate P2Mo 18 The characteristic absorption band appears in the range of 700-1100 cm -1 At 1078cm -1 、1002cm -1 、939cm -1 、905cm -1 and 777cm -1 Its characteristic peak appears at 1078cm -1 and 1002cm -1 The absorption peak can be attributed to PO vibration, 939cm -1 The peak at 905cm can be attributed to the characteristic peak of Mo=O. -1 and 777cm -1 The two peaks are generated by the vibration of the bridging oxygen bond of Mo-O-Mo. Infrared spectrum analysis shows that the synthesized heteropoly compound is a typical P2Mo 18 Dawson-type polyoxometalates.

[0067] from Figure 6 It can be seen that polyoxometalate P2Mo 18 The main absorption peak appears in the range of 200-550nm, and its light absorption range is significantly expanded compared with the 200-350nm of Keggin-type polyoxometalates. This can make the energy utilization rate of the entire polyoxometalate to sunlight higher, and can further improve the photocatalytic performance of the polyoxometalate. The UV-visible spectrum is converted using the Kubelka-Munk equation to obtain P2Mo 18 The band gap energy diagram is shown in Figure 7 As shown, from Figure 7 P2Mo 18 The band gap width of polyoxometalates is 2.39 eV, which is consistent with the range of band gap widths of common polyoxometalates.

[0068] Depend on Figure 8 It can be seen that polyoxometalate P2Mo 18 It mainly exists in the form of rods, some of which are blocky and aggregated together to form a cluster-like state.

[0069] Depend on Fig. 9 It can be seen that the first reduction potential measured by cyclic voltammetry can determine the position of the lowest unoccupied molecular orbital (LUMO) of the material.

[18] From the figure, it can be calculated that the heteropoly acid P2Mo 18 The LUMO of heteropolyacid P2Mo is 0.37V, which is close to the valence band position of conventional polyoxometalates. Combined with the band gap width of 2.39eV obtained from the band gap energy diagram determined by the KM equation, the 18 The highest occupied molecular orbital (HOMO) of is 2.76V.

[0070] (3) Preparation of ferric oxide / phosphomolybdic acid composite material:

[0071] Weigh five portions of P2Mo prepared in (1) 18 1.0g of each was dissolved in 20mL of water, and 0.01g, 0.03g, 0.05g, 0.08g, and 0.10g of Fe2O3 prepared in (2) were added respectively, and the mixture was stirred thoroughly. After a period of time, 20mL of 0.1mol / L tetrabutylammonium bromide aqueous solution was added dropwise, and the reaction was continued for 24h. After the reaction was completed, the mixture was centrifuged and washed with deionized water and ethanol to obtain composite materials of different proportions, which were dried in an oven at 40°C to obtain the target product of ferric oxide / phosphomolybdic acid.

[0072] The ferric oxide / phosphomolybdic acid composite material prepared in this embodiment is characterized mainly by Fourier transform infrared spectroscopy, ultraviolet visible spectroscopy, X-ray powder diffraction, scanning electron microscopy, photoluminescence spectroscopy, and electrochemical impedance spectroscopy. The infrared spectra of different ratios of ferric oxide / phosphomolybdic acid are shown in FIG. Fig.10 As shown, the UV-visible spectra of different ratios of ferric oxide / phosphomolybdic acid are as follows Fig.11 As shown, the X-ray powder diffraction patterns of different ratios of ferric oxide / phosphomolybdic acid are as follows Fig.12 As shown, the scanning electron microscope image of ferric oxide / phosphomolybdic acid is as follows Fig.13 As shown, the photoluminescence spectra of different ratios of ferric oxide / phosphomolybdic acid are as follows Fig.14 The Nyquist and Bode plots of different ratios of ferric oxide / phosphomolybdic acid are shown in Fig.15 As shown, the infrared spectra of the composite materials prepared by Fe2O3 with different reaction times are shown in Fig.16 As shown, the UV-visible spectra of the composite materials prepared by Fe2O3 with different reaction times are shown in Fig.17 As shown, the photoluminescence spectra of the composite materials prepared by Fe2O3 with different reaction times are shown in Fig.18 As shown in the figure, the Nyquist and Bode diagrams of the composite materials prepared by Fe2O3 with different reaction times are shown in Fig.19 shown.

[0073] Depend on Fig.10 It can be seen that using 1%, 3%, 5%, 8%, and 10% Fe2O3 and P2Mo 18 Composite, P2Mo in composite materials 18 The infrared absorption peak positions of -1 、1002cm -1 、939cm -1 、905cm -1 and 777cm -1 Its characteristic peak appears at

[10] .1078cm -1 and 1002cm -1 The absorption peak at 939cm is attributed to PO vibration. -1 The absorption peak at 905cm can be attributed to the characteristic peak of Mo=O. -1 and 777cm -1 The two absorption peaks are generated by the vibration of the bridging oxygen bond of Mo-O-Mo. The infrared results show that the synthesized product is pure phase P2Mo 18 Polyoxometalates.

[0074] Depend on Fig.11 It can be seen that with the increase of Fe2O3 proportion, the intensity of the spectrum at 500-600nm gradually increases. 18 The composite can effectively expand the light absorption range of the material to 700nm, improve the utilization rate of visible light, and promote the photocatalytic reaction.

[0075] Depend on Fig.12 It can be seen that when tetrabutylammonium bromide is added, the secondary structure of the polyoxometalate changes, resulting in P2Mo 18The X-ray powder diffraction patterns of tetrabutylammonium bromide and ammonium chloride are different. The diffraction peak intensity is weakened and the half-peak width of the diffraction peak is increased, and the maximum absorption peak position is slightly blue-shifted. Since polyoxometalates account for more than 90% of the composite material, and the diffraction peaks of polyoxometalates are usually strong, the characteristic peak PDF#99-0060 of ferric oxide is easily masked by polyoxometalates, but the typical diffraction of ferric oxide can still be observed in the diffraction peak of the composite material, as shown in the ※ mark in the figure. This proves that ferric oxide is successfully loaded on the polyoxometalate carrier and the composite material is successfully prepared.

[0076] Depend on Fig.13 It can be seen that in Fe2O3 and P2Mo 18 The addition of tetrabutylammonium bromide during the compounding process not only changed the secondary structure of the polyoxometalate, but also changed the morphology of the polyoxometalate. The scanning electron microscope test results are shown in the figure. The morphology of the polyoxometalate changes from the rod-like shape of the ammonium salt to the block-like shape of the tetrabutylammonium bromide salt. Since the morphology of the composite polyoxometalate is a large block, it is difficult to find the existence of flaky Fe2O3 from many blocky heteropoly acids.

[0077] Depend on Fig.14 It can be seen that the composite material ferric oxide / phosphomolybdic acid was subjected to a photoluminescence test with an excitation wavelength of 401nm. The test results are shown in the figure. The fluorescence emission peaks of all samples are at 600nm. In the photoluminescence test, generally the higher the spectral intensity of the photoluminescence, the higher the probability of recombination of photogenerated holes and photogenerated electrons, and the photocatalytic performance is relatively poor. On the contrary, the composite material with lower photoluminescence spectral intensity has better photocatalytic performance. As can be seen from the figure, when the proportion of Fe2O3 in the composite material is 1%, 3% and 5%, the photoluminescence intensity gradually decreases with the increase of Fe2O3 loading, and the photoluminescence intensity is lower than the luminescence intensity of pure polyacid, indicating that Fe2O3 and P2Mo 18 The composite can effectively inhibit the recombination of photogenerated holes and photogenerated electrons. When the proportion of Fe2O3 increases to 8% and 10%, the photoluminescence intensity increases with the increase of Fe2O3 proportion. This shows that when Fe2O3 is too high, Fe2O3 will partially agglomerate, which will hinder the directional migration of photogenerated carriers, and the probability will gradually increase. The photoluminescence test results show that the composite material with a Fe2O3 loading of 5% has the lowest fluorescence peak intensity, indicating that the composite material with a Fe2O3 loading of 5% has the best inhibitory effect on the recombination of photogenerated holes and photogenerated electrons, the best migration efficiency of photogenerated carriers, and the best photocatalytic effect.

[0078] Depend on Fig.15It can be seen that the proportions of Fe2O3 are 1%, 3%, 5%, 8% and 10% respectively. Usually, the size of the arc in the electrochemical AC impedance Nyquist diagram indicates the size of the electron transfer resistance in the composite material. The smaller the arc radius of the material, the smaller its charge transfer resistance and the better the photocatalytic reaction performance. Therefore, through the electrochemical test results, it was found that the charge transfer resistance of the composite material without the addition of tetrabutylammonium bromide is greater than that of the composite material with the addition of tetrabutylammonium bromide. When the Fe2O3 content is 5%, the radius of curvature of the AC impedance Nyquist diagram is the smallest, indicating that the charge transfer resistance of the composite material is the smallest. The charge transfer resistance when the Fe2O3 ratio is 1% and 3% is greater than that when it is 5%. As the Fe2O3 content continues to increase, the charge transfer resistance of the composite material decreases, and the carrier transport performance of the composite material improves accordingly. When the Fe2O3 content is 8% and 10%, with the increase of Fe2O3 content, Fe2O3 partially agglomerates, forming an electrostatic shielding effect in the local area of ​​the composite material, thereby correspondingly increasing the charge transfer resistance of the composite material and inhibiting the effective transmission of carriers. The electrochemical impedance data is fitted by simulating the circuit, and the impedance of the composite material is represented by the resistance of the circuit element. The results show that the resistance of the composite material is 591.7Ω ​​without adding tetrabutylammonium bromide, 401.1Ω when Fe2O3 accounts for 1%, 305.9Ω when Fe2O3 accounts for 3%, 274.9Ω when Fe2O3 accounts for 5%, 299.4Ω when Fe2O3 accounts for 8%, and 313.6Ω when Fe2O3 accounts for 1%, 3%, 5%, 8%, and 10%. Generally, the better the conductivity of the material, the lower the modulus value in the Bode diagram. It can be seen from the figure that the performance of the composite material with tetrabutylammonium bromide added is better than that of the composite material without tetrabutylammonium bromide. In the comparison of composite materials with different proportions, the modulus value of the composite material with 5% proportion is the lowest, indicating that this material has the fastest carrier transfer rate. Combining the analysis results of Nyquist diagram, Bode diagram and simulation circuit calculation, it is concluded that the addition of tetrabutylammonium bromide is beneficial to the 18 The composite can also improve the migration of carriers at the interface of two different semiconductors in its composite material, and the electrochemical performance of the composite material is best when Fe2O3 accounts for 5%.

[0079] Depend on Fig.16 It can be seen that the Fe2O3 and P2Mo prepared by 2h, 6h, 12h, 18h, 24h 18 The composite material was composited, and the Fe2O3 loading ratio in the composite material was 5%. The infrared spectra of the ferric oxide / phosphomolybdic acid composite material at different reaction times were measured. 18The infrared absorption peak position of the prepared composite material ferric oxide / phosphomolybdic acid appears at 700-1100 cm -1 Polyoxometalate P2Mo 18 The characteristic absorption bands are mainly between 700 and 1100 cm -1 range, including 1078cm -1 、1002cm -1 、939cm -1 、905cm -1 and 777cm -1 Its characteristic peak appears at 1078cm

[17] . -1 and 1002cm -1 The typical absorption peak at 939cm -1 The characteristic peak at 905cm can be attributed to Mo=O. -1 and 777cm -1 Both absorption peaks are caused by the vibration of the bridging oxygen bond of Mo-O-Mo.

[0080] Depend on Fig.17 It can be seen that the Fe2O3 and P2Mo prepared when the reaction time is 12h 18 The UV-visible spectrum of the composite material obtained by the composite is the strongest, indicating that the Fe2O3 and P2Mo prepared when the reaction time is 12h 18 The composite material obtained by compounding has the best performance.

[0081] Depend on Fig.18 It can be seen that when the photoluminescence test was carried out with 401nm as the excitation wavelength, all samples had obvious fluorescence emission at about 600nm. The photoluminescence test results are as follows: Fig.18 This example studies the Fe2O3 and P2Mo prepared by 2h, 6h, 12h, 18h, and 24h. 18 The Fe2O3 content in the composite material is 5%. Fig.18 It can be seen that the Fe2O3 sheet prepared in 12h is similar to P2Mo 18 The composite material obtained by the composite can most effectively inhibit the recombination of photogenerated electrons and photogenerated holes, indicating that the composite material has potential photocatalytic response.

[0082] Depend on Fig.19 It can be seen that in order to further illustrate the composite material, Fe2O3 prepared by different reaction times and heteropoly acid ion P2Mo 18The migration efficiency of the photogenerated carriers of the composite material obtained by loading was studied in detail in this example. The Fe2O3 and P2Mo prepared by 2h, 6h, 12h, 18h, and 24h 18 The composite materials were compounded, and the proportion of Fe2O3 in the composite materials was 5%. The Nyquist curve of the composite material ferric oxide / phosphomolybdic acid was measured. The results of electrochemical analysis show that in composite materials with the same proportion of Fe2O3, as the time required for the preparation of Fe2O3 nanoblocks gradually increases, the resistance of the composite material shows a trend of first decreasing and then increasing. The composite material ferric oxide / phosphomolybdic acid obtained by compounding with Fe2O3 prepared with a reaction time of 12h has the smallest charge transfer resistance. Combined with the electron microscopy characterization results of Fe2O3 nanoparticles, it can be found that the particle size of Fe2O3 nanoparticles that is too small or too large is not conducive to the transmission of carriers in the composite material. The electrochemical impedance data was fitted by a simulation circuit, and the resistance of the circuit element was used to represent the impedance of the composite material. The results show that the Fe2O3 prepared with a reaction time of 2h, 6h, 12h, 18h, and 24h is comparable to P2Mo 18 The resistances of the composite materials were 533.4Ω, 494.6Ω, 274.9Ω, 428.9Ω and 496.7Ω respectively. In addition, the lower the modulus value in the Bode curve, the better the electronic transmission performance of the material. Fig.19 It can be seen that the Fe2O3 and P2Mo 18 Among the composite materials, the composite material obtained by compounding with Fe2O3 prepared for 12h has the lowest modulus and the fastest electron transfer rate. Combining the Nyquist diagram, Bode diagram and simulation circuit calculation results, the composite material obtained by compounding with Fe2O3 prepared for 12h has the best electron transfer performance.

[0083] It can be seen from Example 1 that when the Fe2O3 ratio is 5%, the Fe2O3 prepared for 12 hours and the P2Mo 18 The composite material obtained by compounding has the best performance.

[0084] Example 2

[0085] (1) Preparation of Fe2O3 nanoparticles:

[0086] Dissolve 0.278g FeSO4·7H2O and 0.246g CH3COONa in 40mL deionized water and stir for a while. Transfer the solution to a reactor and heat at 140℃. Adjust the reaction time and the heating time is 12h. After cooling the reactor to room temperature, centrifuge, wash with deionized water and anhydrous ethanol, and dry in an oven at 40℃. Transfer the sample to a crucible and place it in a muffle furnace for calcination. Calcinate at 500℃ for 2h to obtain Fe2O3 nanoparticles with different morphologies.

[0087] (2) Preparation of Dawson-type phosphomolybdic acid P2Mo 18 :

[0088] Dissolve 50g Na2MoO4·2H2O in 225mL deionized water, add 14ml 85% H3PO4, then add 5ml concentrated hydrochloric acid to acidify, heat and reflux for 10h. After the solution is cooled to room temperature, add a certain amount of NH4Cl to crystallize P2Mo 18 The ammonium salt of Dawson type phosphomolybdic acid P2Mo was obtained by repeatedly adding NH4Cl for recrystallization and drying the sample at 40°C. 18 .

[0089] (3) Preparation of ferric oxide / phosphomolybdic acid composite material:

[0090] Weigh the P2Mo prepared in (1) 18 1.0 g was dissolved in 20 mL of water, and 0.05 g of Fe2O3 prepared in (2) was added and stirred thoroughly. After a period of time, 20 mL of 0.1 mol / L tetrabutylammonium bromide aqueous solution was added dropwise, and the reaction was continued for 24 h. After the reaction was completed, the mixture was centrifuged and washed with deionized water and ethanol to obtain composite materials of different proportions, which were dried in an oven at 40 °C to obtain the target product, ferric oxide / phosphomolybdic acid composite material.

[0091] Example 3

[0092] The ferric oxide / phosphomolybdic acid composite material prepared by the present invention can be used as a catalyst for the photocatalytic degradation of methylene blue. The photocatalytic oxidation performance of the ferric oxide / phosphomolybdic acid composite material is studied below. The ferric oxide / phosphomolybdic acid composite material used in this example is prepared in Example 2.

[0093] In the experiment of photocatalytic degradation of organic dyes, spectrophotometry was used for research. The organic dyes were tested by scanning the full band from 200 to 800 nm to determine the maximum absorption wavelength. The degradation rate formula was then used to calculate the degradation effect of the organic dyes.

[0094] Degradation rate calculation formula:

[0095] η=(c0-ct) / c0×100%

[0096] Where η— represents the degradation rate of dye;

[0097] c0—indicates the initial concentration of methylene blue dye (mg / L);

[0098] c t —Indicates the concentration of the dye when the illumination time is t (mg / L);

[0099] Photocatalysis uses a 1000W xenon lamp as the light source. The container uses 200mL quartz photocatalytic reaction hydrazine. 100mL of dye is measured with a measuring cylinder and poured into the quartz reaction hydrazine. 100mg of composite material is added, and a magnetic stirrer is used for rapid stirring. A xenon lamp is placed in the condensation water jacket to cool the xenon lamp. Before turning on the light, dark light stirring is performed for 30 minutes to achieve adsorption equilibrium between the catalyst and the methylene blue dye. After that, the xenon lamp is turned on for irradiation. The reaction lasts for 90 minutes, the sampling interval is 10 minutes, and the sampling volume is about 5mL / time for photocatalytic performance and mechanism research. The study found that the photocatalytic performance of the composite material is related to a variety of influencing factors. During the experiment, the types of dyes were first screened, and then the reaction conditions such as dye concentration, catalyst dosage and pH were explored. In addition, a variety of masking agents were introduced to explore the photocatalytic reaction mechanism in detail.

[0100] Four parallel experiments were designed with methylene blue, eosin B, rhodamine B and methyl orange as substrates. Fig. 20 It can be seen that the catalyst has a more obvious degradation effect on the substrate. The dark light adsorption efficiency of the four substrates is relatively ideal, but the final degradation rate of Eosin B can only reach about 60% during the photocatalytic degradation process, while the photocatalytic efficiency of Rhodamine B and Methyl Orange is even lower, only reaching about 30% and 20%. The final treatment effect of methylene blue can reach 98.58%, which is the most ideal. Therefore, among the above four organic dyes, methylene blue was selected as a model reaction to study the photocatalytic performance of the composite material.

[0101] Four parallel experiments were designed with initial methylene blue concentrations of 5 mg / L, 10 mg / L, 20 mg / L, and 30 mg / L. Fig.21 As shown in (a), the photocatalytic decomposition shows an obvious trend of change. When the concentration of substrate methylene blue is 5 mg / L, 10 mg / L, and 20 mg / L, the photocatalytic degradation effect is better than when the concentration of methylene blue is 30 mg / L, and the photocatalytic decomposition is above 98%. Fig.21As shown in (b), through the fitted reaction rate diagram, it can be found that the degradation rate constant of 5 mg / L methylene blue is 0.0216, the degradation rate constant of 10 mg / L methylene blue is 0.02929, the degradation rate of 20 mg / L methylene blue is 0.03231, and the degradation rate constant of 30 mg / L methylene blue is 0.00313, which proves that the initial concentration of 20 mg / L methylene blue is conducive to the catalytic reaction and the reaction rate is the fastest.

[0102] In the comparative photocatalytic experiments of different catalysts, the condition of using only xenon lamp for illumination is the most control experiment, such as Fig. 22 As shown in (a), methylene blue has no obvious decomposition. Under the condition of Fe2O3 as a catalyst, the degradation trend of methylene blue is also not obvious, only about 2%. In the composite material ferric oxide / phosphomolybdic acid, the photocatalytic effect of the composite materials with Fe2O3 accounting for 1% and 10% is relatively poor, and the photodegradation rate of methylene blue is only about 74% and 70%. The catalytic efficiency of the composite materials with Fe2O3 accounting for 3%, 5%, and 8% is relatively high, reaching more than 95%, among which the composite material with Fe2O3 accounting for 5% has the best photocatalytic effect, which can reach 98.98%. Similarly, Fig. 22 As shown in (b), from the photocatalytic degradation rate, it can be seen that the composite material with a Fe2O3 content of 5% has the fastest reaction rate, with a rate constant of 0.04373, which is significantly higher than the composite materials with a Fe2O3 content of 3% and 8%. Combining the experimental results of photocatalytic degradation rate and reaction rate, it is found that the composite material with a Fe2O3 content of 5% has the best catalytic performance.

[0103] Then, 7 parallel experiments with pH values ​​ranging from 1 to 7 were designed to explore the effect of pH value on photocatalysis. The photocatalytic rate of methylene blue showed different trends at different pH values ​​(e.g. Fig.23 As shown in (a)), it can be seen from the figure that the dark light adsorption is relatively less affected by pH, and the adsorption amount is in the range of 10% to 20%. This shows that the composite material has good stability, and changes in the hydrogen ion concentration in the solution will not have a significant effect on the structural stability of the composite material. Therefore, the composite material exhibits stable adsorption performance. Under conditions of pH 1 to 7, the photocatalytic degradation rate of methylene blue does not change significantly, which are 98.89%, 98.14%, 98.12%, 98.56%, 98.45%, 98.96% and 98.98% respectively. The photocatalytic rate diagram under different pH conditions ((as shown in Fig.23 As shown in (b)). It can be clearly seen from the figure that the photocatalytic reaction rate under pH 7 is significantly higher than that of the other groups. The reason may be that the presence of hydrogen ions in the solution has an inhibitory effect on the photocatalytic reaction.

[0104] According to the experimental conclusion of this example, the experimental group with pH = 7 was selected to characterize the process of photocatalytic degradation of dye by UV-visible spectroscopy (such as Fig.24 As shown). As the photocatalytic reaction time gradually increases, the ultraviolet spectrum intensity of methylene blue continues to decrease, which indicates that methylene blue is gradually degraded. In addition, the concentration change trend of methylene blue in the photocatalytic process is different within the same time interval. At the beginning of catalysis, due to the high dye concentration, the methylene blue concentration does not change much. As the photocatalytic reaction proceeds, the reaction rate gradually accelerates, the concentration change gradient reaches a maximum value, and tends to stabilize. As the dye concentration gradually decreases, the photocatalytic rate decreases again, which is due to the extremely low concentration of the dye and the reduced number of activated dye molecules adsorbed on the catalyst surface. Until the photocatalytic reaction tends to equilibrium, the final degradation rate of methylene blue is about 98.98%. In summary, the composite material has excellent photocatalytic degradation ability for methylene blue dye at a pH of 7.

[0105] Further, a photocatalytic cycle experiment was conducted, and the data of the ferric oxide / phosphomolybdic acid cycle experiment is shown in the figure below: Fig.25 As shown, the infrared comparison diagram of the ferric oxide / phosphomolybdic acid cycle experiment sample is shown in Figure 26. Fig.25 It can be seen that in the initial experiment, the proportion of dark light adsorption of the catalyst was about 15%, and the degradation rate reached about 99% after the catalysis was completed. During the first cycle, the proportion of dark light adsorption of the catalyst was about 16%, and the degradation rate remained basically unchanged after the catalysis was completed, still reaching 98%. During the second cycle, the proportion of dark light adsorption of the catalyst was about 19%, and the degradation rate still reached 96% after the catalysis was completed. In the three-cycle experiment, the proportion of dark light adsorption of the catalyst was about 29%, and the degradation rate remained at a high level of about 94% after the catalysis was completed. During the entire cycle experiment, it can be seen that the proportion of the dark light adsorption peak of the catalyst has increased, and the degradation rate after the catalysis has decreased slightly, but the overall trend has not changed significantly and remains stable, proving that the catalyst still maintains good catalytic stability during the three cycles.

[0106] The catalyst activation experiment firstly removes most of the organic residues by calcining at 200°C. Secondly, it is treated by repeated washing with deionized water / anhydrous ethanol. Finally, the ethanol-treated composite material is irradiated under ultraviolet light for a period of time to complete the catalyst activation process. The infrared characteristic peaks of the activated composite material are consistent with those of the composite material before activation ( Fig.26 ), at 1078cm -1 and 1002cm -1 PO antisymmetric stretching vibration peak at 939 cm -1 The antisymmetric stretching vibration peak at 905 cm -1 and 777cm -1The Mo-O-Mo bridging oxygen bond vibration peak at is exactly the same as before activation. At the same time, no characteristic peak of methylene blue is found in the activated composite material. Therefore, we believe that the composite material is successfully activated.

[0107] From the above experiments, it can be seen that the optimal photocatalytic reaction conditions of the composite catalyst ferric oxide / phosphomolybdic acid are: Fe2O3 accounts for 5%, solution pH = 7, and dye concentration is 20 mg / L. Under these conditions, isopropanol, triethanolamine and p-benzoquinone were added as masking agents to explore the photocatalytic reaction mechanism ( Fig. 27 ). In the photocatalytic mechanism test, triethanolamine was used as a masking agent for photogenerated holes, isopropanol as a masking agent for hydroxyl radicals, and para-benzoquinone as a masking agent for superoxide radicals. As can be seen from the figure, under the condition of adding isopropanol, the photocatalytic performance of the composite material decreased by 60%, proving that hydroxyl radicals are the cause of the degradation of methylene blue. Under the condition of masking the photogenerated holes, the final catalytic result is still very high, with no obvious changes, proving that in the process of catalytic degradation of methylene blue, photogenerated holes cannot affect the photocatalytic results. Under the condition of adding para-benzoquinone, superoxide radicals are masked, and the final photocatalytic results remain unchanged. Therefore, superoxide radicals cannot affect the photocatalytic decomposition of methylene blue. In summary, we can conclude that in the experiment of photocatalytic decomposition of methylene blue by composite material ferric oxide / phosphomolybdic acid, the main factor affecting the photocatalytic rate is hydroxyl radicals.

[0108] Fe2O3 can cyclic voltammetry test diagram and band gap diagram as shown in Fig.28 As shown, according to Fig.28 It can be seen that the conduction band position of Fe2O3 is around 0.29V, the band gap width is about 2.02eV, and the valence band position of Fe2O3 is around 2.31V. It can be seen that the LUMO position of heteropoly acid is around 0.37V, the band gap width is about 2.39eV, and the HOMO position of heteropoly acid is 2.76V. Based on the above information, the photocatalytic mechanism diagram of the composite material is drawn ( Fig.29 ).

[0109] Under the condition of simulated sunlight irradiation, the electron-hole pairs of polyoxometalates are separated, and the photogenerated electrons generated in the polyoxometalates transition from HOMO to LUMO. The electron-hole pairs of Fe2O3 are also separated, and the photogenerated electrons transition from the valence band to the conduction band across the forbidden band. The photogenerated electrons on the LUMO of the polyoxometalates are quenched by the holes on the valence band of Fe2O3. This indirectly increases the band gap width of the composite material, effectively preventing the recombination of photogenerated electrons and photogenerated holes, thereby further improving the photocatalytic performance. The inferred reaction mechanism is as follows:

[0110] Iron(III) oxide / phosphomolybdic acid+hv→Fe2O3(e - ) / P2Mo 18 (h + )

[0111] H2O+h + →H + + · OH

[0112] MB+ · OH → Final product

[0113] It can be concluded that the photocatalytic degradation of methylene blue by ferric oxide / phosphomolybdic acid mainly depends on the action of hydroxyl radicals. Combining the active group masking experiment and the photocatalytic mechanism diagram, it is speculated that superoxide radicals do not participate in the photocatalytic process during the photocatalytic reaction. First, in the masking agent experiment, the photocatalytic effect was almost unchanged after the addition of benzoquinone to mask the superoxide radicals. Secondly, by calculating the valence band position of the composite material, since the position of the catalyst band gap failed to reach the electrode potential for superoxide radical conversion, superoxide radicals would not be generated in the reaction system of the catalyst. After the addition of isopropanol, the photocatalytic effect decreased significantly, indicating that hydroxyl radicals play a major role in catalysis. Therefore, hydroxyl radicals can only be generated through the only conversion path of photogenerated holes reacting with water. Finally, methylene blue is oxidized by hydroxyl radicals, thereby achieving the purpose of degrading methylene blue.

[0114] Example 4

[0115] The ferric oxide / phosphomolybdic acid composite material prepared by the present invention can be used as a catalyst for photocatalytic degradation of potassium dichromate. The photocatalytic reduction performance of the ferric oxide / phosphomolybdic acid composite material is studied below. The ferric oxide / phosphomolybdic acid composite material used in this example is prepared in Example 2.

[0116] The photocatalytic reduction performance of the ferric oxide / phosphomolybdic acid composite material was taken as an example to degrade potassium dichromate. The spectrophotometric method was used to test potassium dichromate using a full-band scan from 200 to 800 nm, and the maximum absorption wavelength was determined to be 365 nm. The degradation rate formula was then used to calculate the degradation effect of potassium dichromate.

[0117] Photocatalysis uses a 1000W xenon lamp as a light source. The container uses 200mL quartz photocatalytic reaction hydrazine. 100mL of potassium dichromate solution is measured with a measuring cylinder and poured into the quartz reaction hydrazine. 100mg of the composite material is added and stirred rapidly with a magnetic stirrer. Stirring in dark light for 30 minutes before turning on the light allows the catalyst and potassium dichromate to reach adsorption equilibrium. Turn on the xenon lamp for irradiation, the reaction duration is 90 minutes, the sampling interval is 10 minutes, the sampling volume is 4 to 5mL each time, and the 721 spectrophotometer and UV-visible spectrum are used for measurement.

[0118] The photocatalytic performance of composite materials is related to a variety of influencing factors. During the experiment, I explored the reaction conditions such as potassium dichromate concentration, different proportions of catalysts, and pH of the catalytic reaction. I also introduced a variety of masking agents, explored the photocatalytic reaction mechanism, and conducted cyclic experimental tests on the catalyst.

[0119] For the experiment on the effect of different concentrations of potassium dichromate on photocatalysis, four parallel experiments were designed with substrates of 20 mg / L, 50 mg / L, 100 mg / L, and 200 mg / L ( Fig.30 ).from Fig.30 It can be seen that the degradation rate of potassium dichromate at 100mg / L and 200mg / L in the photocatalytic reaction is extremely low, only reaching 15% and 7%, and the adsorption is basically 0, the effect is poor, indicating that the composite material has no obvious degradation effect on high-concentration chromium-containing solution. In the photocatalytic reaction of potassium dichromate at 50mg / L and 20mg / L, the final degradation rate is almost the same, both can reach 38%. In comparison, the adsorption is lower under the condition of 50mg / L, so the catalytic efficiency is higher under the condition of 50mg / L. It can be seen from the figure that with the decrease of potassium dichromate concentration, the photocatalytic efficiency increases, but the photocatalytic efficiency does not continue to increase with the continuous decrease of potassium dichromate concentration. When the concentration of potassium dichromate decreases from 50mg / L to 20mg / L, the photocatalytic efficiency does not increase, so the subsequent experiments are carried out with 50mg / L potassium dichromate.

[0120] Data comparison of photocatalytic reactions of different catalysts under 50 mg / L potassium dichromate ( Fig.31 ).from Fig.31 It can be seen that the degradation rate can reach 3% without adding a photocatalyst. When Fe2O3 is used as a catalyst, the degradation rate is slightly improved to about 6%. When using composite materials with different proportions as photocatalysts, the photocatalytic degradation efficiency is between 30% and 40%. The composite material with 5% Fe2O3 has the highest catalytic degradation efficiency, reaching 38%. It can be seen that the performance of Fe2O3 alone as a photocatalyst is poor, and it has almost no promoting effect on photocatalysis. When Fe2O3 and P2Mo18 After compounding, the composite material has a more obvious promoting effect on photocatalysis, and the final photocatalytic degradation rate also conforms to the rule that the proportion of Fe2O3 in the composite material gradually increases from 1% to 5%, and then decreases from 5% to 10%. This phenomenon also matches the conclusions obtained from electrochemical impedance spectroscopy and photoluminescence spectroscopy.

[0121] Data of photocatalytic degradation of potassium dichromate at different pH values ​​( Fig.32 ). The pH of potassium dichromate solution was adjusted by hydrochloric acid or sodium hydroxide solution. It can be seen from the figure that the degradation of potassium dichromate is difficult to proceed under both acidic and alkaline conditions, and the final degradation rate is less than 10%. Only under the neutral condition of pH = 7, there is a more obvious photocatalytic degradation, and the final degradation rate can reach 38%.

[0122] Through the experiment of this embodiment, it can be known that the optimal photocatalytic conditions of ferric oxide / phosphomolybdic acid are: the Fe2O3 ratio of the catalyst is 5%, the solution pH = 7, and the potassium dichromate concentration is 50mg / L. According to the study of the mechanism of photocatalytic degradation of methylene blue by ferric oxide / phosphomolybdic acid composite materials, the electrode potential of the conversion of oxygen and superoxide radicals is not within the band gap of the composite material, so that no reaction can occur to generate hydroxyl radicals. Therefore, when testing the photocatalytic mechanism of potassium dichromate, it is only necessary to mask the photogenerated holes and hydroxyl radicals, and there is no need to mask the superoxide radicals ( Fig.33 ). When the pH is equal to 7, the masking agents methanol and isopropanol are added, and the photocatalytic efficiency is slightly improved. When the pH is equal to 5, the addition of methanol significantly increases the photocatalytic effect, while the addition of isopropanol only slightly improves it. This is because the addition of isopropanol masks hydroxyl radicals. The reduction of hydroxyl radicals will reduce the reaction between hydroxyl radicals and photogenerated electrons, thereby increasing photogenerated electrons. Photogenerated electrons react with potassium dichromate to increase the degradation rate of potassium dichromate.

[0123] After adding methanol to the potassium dichromate solution, the photocatalytic degradation efficiency was still very low, less than 10% ( Fig.34). As the pH value decreases, the efficiency of photocatalysis increases. When the pH value is 9, the degradation rate reaches 22%, and when the pH value is 7, the degradation rate reaches 53%. As the pH value further decreases, the degradation rate of photocatalysis can reach more than 94%. The final degradation rates of photocatalysis are almost the same at pH 3 and 5, reaching 95 and 96% respectively. As the pH increases, the oxidation ability of dichromate decreases, and it is more difficult for the catalyst to produce electron-hole pairs under alkaline conditions, so the photocatalytic effect continues to decline when the pH is 9 to 13. When the pH is 7, the photocatalytic effect is not obvious. The reason for this is that there are neither hydrogen ions in the solution to promote the reaction nor hydroxides to inhibit the reaction. When the pH is less than 7, the addition of methanol to the potassium dichromate solution will greatly improve the efficiency of the photocatalytic reaction. At pH 3 and 5, the trends of the photocatalytic reactions are basically the same. When the pH is equal to = 1, the photocatalytic rate slows down, but the degradation rate of potassium dichromate reaches its maximum value. Although dichromate is more oxidizing when the acidity is stronger, and it is easier to generate photogenerated electrons under acidic conditions. However, due to the strong acidity, more electron-hole pairs will be generated under the condition of pH equal to 1, and the presence of methanol is not enough to completely mask the photogenerated holes. Therefore, under the condition of pH equal to 1, some photogenerated electrons will recombine with photogenerated holes, resulting in a decrease in the rate of photocatalysis. Therefore, under the condition of similar degradation rates, considering the important factor that a strong acidic environment is not conducive to the stability of the catalyst, this experiment uses a milder reaction condition of pH 5 for the photocatalytic reaction.

[0124] Photocatalytic data of different catalysts at pH 5 with methanol added ( Fig.35 ). When no catalyst is added, the photocatalytic degradation rate is 13%, and the degradation rate reaches 22% when Fe2O3 is added as a catalyst. When composite materials with different Fe2O3 loading ratios are added, the degradation rate varies from 56% to 96%, among which the 5% composite material has the highest catalytic efficiency, which can reach 96%. It can be concluded that under the condition of pH 5, adding methanol to 50mg / L potassium dichromate solution and adding 100mg of Fe2O3 with a 5% composite catalyst can achieve the best catalytic effect, and the degradation rate can eventually reach 96%.

[0125] In order to investigate the cyclic stability of the composite catalyst, a photocatalytic cycle experiment was carried out. Fig.36. In the initial sample, the dark light adsorption effect reached 9%, and 96% could be degraded after the reaction reached equilibrium. The dark light adsorption in one cycle was 10%, and the final degradation reached 94%. The dark light adsorption in the second cycle was 12%, and the final degradation was 92%. The dark light adsorption in the third cycle was 15%, and the final degradation was 90%. It can be seen that the composite material basically maintains stable photocatalytic activity during the cycle process and is a high-quality photocatalytic material. The infrared characteristic peaks of the composite material after activation are consistent with those of the composite material before activation ( Fig.37 ), at 1078cm -1 and 1002cm -1 PO antisymmetric stretching vibration peak at 939 cm -1 The antisymmetric stretching vibration peak at 905 cm -1 and 777cm -1 The vibration peak of the Mo-O-Mo bridge oxygen bond at 400 nm is exactly the same as that before activation. At the same time, no characteristic peak of methylene blue is found in the composite material after activation. Therefore, it is considered that this method is successful for the activation of the composite material.

[0126] Under the condition that methanol is added to mask the photogenerated holes, the introduction of hydrogen ions will make the photocatalytic reaction proceed better. At the same time, the oxidation ability of dichromate ions gradually increases with the increase of acidity, which is conducive to the occurrence of photocatalytic reactions. Under acidic conditions, it is conducive to the generation of electron-hole pairs. After methanol masks the photogenerated holes, it is difficult for the photogenerated electrons to recombine with the photogenerated holes. Finally, the photogenerated electrons react with potassium dichromate, effectively degrading the potassium dichromate solution ( Fig.38 ), the reaction process is speculated to be as follows:

[0127] Iron(III) oxide / phosphomolybdic acid+hv→Fe2O3(e - ) / P2Mo 18 (h + )

[0128] Fe2O3(e - )+H + +Cr(VI)→Cr(Ш).

[0129] It can be seen from the above-mentioned Examples 3 and 4 that: ① Through the test of photocatalytic degradation of methylene blue, it is proved that the ferric oxide / phosphomolybdic acid composite material can effectively degrade methylene blue dye with a concentration below 20 mg / L, and the optimal experiment is pH=7, and the Fe2O3 in the composite material accounts for 5%. Under the optimal conditions, the final degradation rate of methylene blue can reach 99%. The activated ferric oxide / phosphomolybdic acid composite material still maintains its basic structure and can still maintain its excellent catalytic performance in three cycles. ② The photocatalytic mechanism of the composite material was tested by using triethanolamine, isopropanol, and p-benzoquinone as masking agents, and it was concluded that the active group in the photocatalytic process of the composite material is hydroxyl radicals. By exploring the influence of different masking agents on the photocatalytic effect under different pH conditions, it was found that the reaction mechanism of the composite material will not change with the change of pH. When the pH value is in the range of 1 to 7, the hydroxyl radical is always the main active group for catalytic degradation of methylene blue. ③ Through the photocatalytic reduction study of potassium dichromate aqueous solution, it was found that the degradation rate changed significantly with the change of pH value during the degradation process. At pH 7-13, as the alkalinity increases, the photocatalytic performance continues to decline. Under acidic conditions, the photocatalytic performance is excellent and potassium dichromate can be almost completely degraded. The experimental results show that when 50 mg / L potassium dichromate solution is added with methanol, the composite material catalyst with 5% Fe2O3 can achieve the best degradation effect at pH 5.

[0130] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a ferric oxide / phosphomolybdic acid composite material, characterized in that: The following steps are involved: S1. Preparation of Fe2O3 nanoparticles and Dawson-type phosphomolybdic acid P2Mo 18 ; S2, preparation of ferric oxide / phosphomolybdic acid composite material: take a Dawson type phosphomolybdic acid P2Mo with a weight ratio of 100: (1-10) 18 and Fe2O3 nanoparticles were dissolved in water, stirred and mixed thoroughly, and then 0.1 mol / L tetrabutylammonium bromide aqueous solution was added dropwise, the added volume of the tetrabutylammonium bromide aqueous solution was the same as the mentioned volume of the water, and the reaction was continued for 24 hours. After the reaction was completed, centrifugation was performed, and the mixture was washed with deionized water and ethanol and then dried in an oven at 40°C to obtain an iron trioxide / phosphomolybdic acid composite material.

2. The method for preparing the ferric oxide / phosphomolybdic acid composite material according to claim 1, wherein: The specific steps of preparing Fe2O3 nanoparticles in step S1 are as follows: 0.278 g of FeSO4·7H2O and 0.246 g of CH3COONa were dissolved in 40 mL of deionized water, and the mixture was stirred thoroughly to be uniform. The solution was transferred to a reactor and heated at 140°C for reaction for 2-24 h. After the reactor was cooled to room temperature, it was centrifuged, washed with deionized water and anhydrous ethanol, and then dried in an oven at 40°C. After drying, the mixture was transferred to a crucible, placed in a muffle furnace for calcination, and calcined at 500°C for 2 h to obtain Fe2O3 nanoparticles.

3. The method for preparing the ferric oxide / phosphomolybdic acid composite material according to claim 1, wherein: In step S1, Dawson type phosphomolybdic acid P2Mo is prepared 18 The specific steps are as follows: Dissolve 50g of Na2MoO4·2H2O in 225mL of deionized water, add 13-17ml of 85% H3PO4, and then add 3-6ml of hydrochloric acid to adjust the pH to 1-2. Heat and reflux for 10h. After the solution is cooled to room temperature, add NH4Cl until solid precipitates. Repeat recrystallization to obtain P2Mo 18 The ammonium salt was dried at 40 °C to obtain pure Dawson type phosphomolybdic acid P2Mo 18 .

4. The method for preparing the ferric oxide / phosphomolybdic acid composite material according to claim 2, characterized in that: The heating reaction time for preparing the Fe2O3 nanoparticles is 12 hours.

5. The method for preparing the ferric oxide / phosphomolybdic acid composite material according to claim 1, characterized in that: The Dawson type phosphomolybdic acid P2Mo 18 and Fe2O3 nanoparticles in a weight ratio of 100:

5.

6. A ferric oxide / phosphomolybdic acid composite material obtained by the method according to any one of claims 1 to 5.

7. A use of the ferric oxide / phosphomolybdic acid composite material as claimed in claim 6, characterized in that: The ferric oxide / phosphomolybdic acid composite material is used as a catalyst for photocatalytic degradation of methylene blue and / or potassium dichromate.

Citation Information

Patent Citations

  • Preparation and photo-catalytic application of Keggin type saturated phosphomolybdate and coating material of Keggin type saturated phosphomolybdate

    CN107758639A

  • Inorganic structure silicon-tungsten polyoxometallate doped ferric oxide composite nano catalytic material as well as preparation and application of inorganic structure silicon-tungsten polyoxometallate doped ferric oxide composite nano catalytic material

    CN113731418A

  • Titanium dioxide / polyacid / ferric oxide three-layer coaxial nanobelt gas sensing material and preparation method thereof

    CN114314652A